ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMA PADA MATERI PROGRAM LINIER - Afifah Nur Fitriani; Nita Hidayati (IKIP Siliwangi, 2022)
The purpose of this study is to describe the level of mathematical communication skills in linear programming material. Mathematics is an important science to be mastered in the field of education, especially in mathematical communication skills. The research subjects were students of class XI IPA 2 at SMA Negeri 2 Klari in the academic year 2021/2022. In this study using a descriptive method with a qualitative approach. The instrument used is a written test of mathematical communication skills with 5 questions. This test instrument aims to describe the extent to which students are able to explain their ideas mathematically. To obtain descriptive data, data analysis techniques are used, namely by sorting out important data, presenting data, and drawing conclusions. The results obtained indicate that some students are able to explain ideas algebraically, namely by making mathematical models from the graphs of the functions presented, can determine inequality models in graph form, are able to solve problems by describing a graph, can answer questions algebraically by grouping the x variable. and y into the form of inequalities, and is able to translate the problem into inequalities, then complete the calculation by substitution. So it can be concluded that students have mathematical communication skills with a high category.